Diversidade de bactérias endofíticas obtidas de solos do oeste do paraná usando milho e trigo como planta isca - Chaves, Elisiane Inês Dall'oglio (2013)
The plant growth promoting bacteria constitute a large group of plant associated microorganisms that has a huge potential to be explored for beneficial contribution in plant growing. In this context, the aim of this work was to study the diversity of endophytic bacteria obtained from soils in western Paraná, using plants such as wheat and corn baits and evaluate the potential of isolates to promote plant growth (PCV). A total of 136 endophytic bacteria isolates were obtaines from roots in three different locations: area 1 (Argissolo vermelho), area 2 (Latossolo vermelho) and area 3 (Nitossolo vermelho). A total of 136 endophytic bacteria strains were isolated from roots in three different locations: area 1 (Argissolo vermelho), area 2 (Latossolo vermelho) and area 3 (Nitossolo vermelho). The isolates were evaluated for their ability to solubilize insoluble phosphate in NBRIP medium and also their ability to synthesize auxin in DYGS medium. Eighty-four bacterial strains were analyzed by molecular analysis of polymorphism by ARDRA and 41 of these fragments were sequenced 16S rDNA. Six isolates randomly chosen were evaluated according to their ability in promoting the plant growth in vitro, where from these, two contrasting isolates were evaluated for their performances in pots. As results for biochemical characterization, from 136 isolates, 51 % showed no phosphate solubilizing capacity, 14 % had a low level of phosphate solubilization index (ISF) low (IS<2), 9.5% medium (IS<4) and 25.5% higher (IS≥4), the higher ISF was verified in UFPRPALM 3-66 (7.66). IAA (indole-3-acetic) values ranged from 19.94 (UFPRPALM1 -134) to 1170.98 mg IAA mg protein-1 (UFPRPALM 2-32) without tryptophan addition and adding this aminoacid , only 42 strains (31%) were able to produce IAA in higher levels ranging from 362.18 (UFPRPALM 3-65) to 5599.57 (UFPRPALM 3-80) mg IAA mg protein -1. The polymorphism analysis revealed by ARDRA bacterial 8 groups with 70% dissimilarity and only 8 isolates showed clonal profile. The sequences of the 16S rDNA allowed the grouping of 41 isolates in eight different phylogenetic groups, among these the bacteria of the genus: Agrobacterium, Shigella, Stenotrophomonas, Enterobacter, Pantoea, Pseudomonas, Ensifer, Brevibacillus, Escherichia, Acinetobacter, Bacillus and Burkholderia. Of these, six isolates producing IAA and P-solubilization ability wich were evaluated for in vitro growth capacity were chosen. Isolated in this experiment, two contrasting were characterized: UFPRPALM 3-87 (Burkholderia ambifaria), more and UFPRPALT 1-14 (Pantoea ananatis), with lower ability to promote the growth of wheat seedlings in vitro, respectively. In the pot experiment, the isolates showed no responses of plant growth promotion in high fertility soils, but at low fertility condition, the genus Pantoea (UFPRPALT 1-14) showed the best performance in terms of increases in nitrogen concentration of shoots in wheat. There was a differential response of the isolates in terms of epiphytic and endophytic microbial population and between plant species and conditions of fertilization and/or inoculation